Are there any differences on the quality attributes of pre - and post-rigor chevon? - Jannat, M; Ruknuzzaman, M; Khan, M; Rahman, M; Hashem, MA (Meat Research, 2023)
The present study was conducted to find out whether pre-rigor and post-rigor state has significant impact on quality attributes of chevon. For this 10 Longissimus dorsi muscles from five Black Bengal goats were collected. Fresh chevon were considered as pre-rigor sample and other five samples were preserved at 4ºC counted as post-rigor samples. Independent t-test was used for analyses the data. The findings demonstrated that among physicochemical characteristics, rigor state had no discernible (p>0.05) impact on water holding capacity (WHC) and cooking loss (CL). However, post-rigor chevon drip loss was substantially higher (p<0.05) than pre-rigor chevon drip loss whereas pH value was significantly (p<0.05) higher in pre-rigor chevon. Higher CIE a*, b*, Hue angle values were found in post-rigor than pre-rigor chevon. Post-rigor chevon had substantially better (p<0.05) flavor, tenderness, texture and general acceptability. On the contrary, pre-rigor chevon's TVC, TCC and TYMC microbial count values were all substantially higher (p<0.05) than those of the post-rigor chevon. So, it can be sum up that, there are notable differences between pre-rigor and post-rigor chevon in a number of physicochemical and sensory properties. Despite having less drip loss of pre-rigor chevon, post-rigor chevon is more palatable and less contaminated by microbes.